TES STANDAR DAN TES BUATAN GURU - Mega Ayu Utamima, M. Abdul Rozak, Eka Widyanti (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
The purpose of this research is to know more about standardized tests and teacher-made tests, understand the uses and differences that exist in standardized tests and teacher-made tests. the research approach uses a qualitative descriptive method. reducing and summarizing data, presenting findings, and drawing conclusions are part of the process of analyzing data. using trigulation of data sources to inform the truth of the information collected. getting good knowledge about standardized tests and teacher-made tests is a clear result of this research.